Opportunity Growth Sport Tourism in the Magetan Regency - Bayu Purwo, Adhi; Rohmad; Wanuh, Wiyarko (STKIP Paasundan Press, 2025)
Currently, sports are experiencing rapid development, evidenced by the increasing number of people participating in sports activities, especially in the field of sports tourism. The research method used is qualitative descriptive. The results of this study indicate that, based on data analysis, Telaga Sarangan has significant potential to be developed as a sports tourism destination. The types of sports with high potential in this area include hiking, jogging, and outbound activities. There are obstacles that need to be addressed, particularly regarding limited equipment and infrastructure conditions. In this context, understanding the role of sport tourism in supporting sustainable economic development and improving the quality of life for the community is essential. The conclusion of this research is that the growth opportunities for sport tourism in Magetan Regency at Telaga Sarangan has a strong potential to develop sports tourism and enhance the tourism sector in Magetan Regency.